Integrating Digital Innovation Mechanisms in Digital Infrastructures: The Case of Digital Remote Care - Anne KS Ajer; Egil Øvrelid (SAGE Publishing, 2023)
Digital innovation (DIN) is crucial for managing the growth of resource use in the hospital sector and for providing citizens with services aligned with the requirements of the modern world. DIN includes the co-creation of novel services, such as digital remote care (DRC) solutions. The healthcare sector, with a plethora of applications, is an example of a large digital infrastructure. Our study aims to explore how DRC initiatives can be integrated in large-scale digital infrastructures. Our in-depth case study, which explores 72 different DRC trajectories at 9 hospital health trusts in Norway, reveals the dynamic interplay among 3 key mechanisms - idealistic entrepreneurship, anchoring and remote infrastructure. Our contribution to the DIN literature is a model that shows the interplay among these key mechanisms, which increases the innovation pace, improves the innovations' scalability and provides a robust organisation that constantly implements innovations. As a contributions to DRC practice, lessons learned to speed up the innovation pace are offered: (1) Create a DRC organisational structure. (2) Ensure financial predictability. (3) secure anchoring upward in the governance structure. (4) Make the remote infrastructure appropriate for integration with the current digital infrastructure. (5) Advocate the success across the organisation to spur others to innovate.